Mídia, ciência e produção de subjetividade : uma análise dos sentidos de saúde no cenário de publicação das leis nº 8.080/90 e nº 8.142/90 - Cadoná, Eliane (2015)
In this thesis, we aimed to understand the meanings produced on health in the press and in scientific journals, in publishing scenario the Organic Health Law, the idea of linking linguistic contexts and historical-political show conditions that made possible the establishment of truths and practices that moment. Such a scenario was marked by contradictory peculiarities, in which a neoliberal policy was subject of a new constitution, guided by participation. Panning meaning in the health field at this moment in Brazilian history means understanding the articulation of modes of existence to the socio-political scenarios that moment. To answer the research objectives, we incorporated the same in three steps, which led to the formulation of three articles. We emphasize that the theoretical bases used in this study were those inspired by the perspectives adopted by Social Constructionism. In the first study, entitled Social Constructionism in Basic Care: An Integrative Review propose the analysis of scientific papers, with the purpose of investigating how authors who rely on Social Constructionism define health in Basic Care. The authors of these materials claim that it is possible to expand health practices for collective action that enables ongoing dialogue between users and health workers. We also point out, in the study, the criticism of the predominance of speech biomedical promoter glued to centralized logic of care practices in disease. In the second study, entitled Concepts of Health Care in the Brazilian Print Media: An Analysis of the Year 1990 about the perspective the Newspapers Zero Hora problematize health care senses and carefully produced in print through the study of discursive practices. The corpus of the research consisted the analysis of the newspapers Zero Hora daily publication onveyed along the year 1990. Altogether, 365 papers were analyzed. With this study, it was possible that they were put in the newspapers, logical a period of national history strongly marked by health concepts related to the absence of disease. And care practices linked to population control measures. We realize that the citizen, the Brazilian already worshiped, in 1990. A perspective the preventative brand and care practices, much more worried with the interests of the ruling class than with the health of the population as a whole, with pattern watchful to particulars and contexts defined by labor market logic. The newspaper Zero Hora, in the midst of this scenario, assumes the role of producer of a model citizen linked to neoliberalism, emphasizing the primacy of private health services on public, and hospital centered model of care. In the third study, entitled Science and Production Meaning: An Analysis of Brazilian Academic Research in the Context of Publication of Organic Laws of Health. We put under review meaning health analysis shared in scientific production, published in 1990, in Brazil. They were recovered from the Virtual Health Library Brazil 34 articles, submitted to Discourse Analysis. From the analysis of the constitution, we realize that the speeches made in the studies carried the logic that knowledge imported, stemming the so-called industrialized countries, it should be the rule to follow in Brazil and the printed reality these scenarios would serve as a model of inspiration for the same. It was also evident the emphasis on research that highlighted the concern for the physical and experimental studies, in contrast with other concepts that question and the way health practices were being experienced. The doctor's figure is highlighted denouncing the contradiction between Brazilian Legislation and practices in health that scenario in which justifies exercises with an emphasis on healing and the monopoly of knowledge. To connect the data collected in this research, in general, evidenced health notions linked to the absence of disease, the cult of physical health at the expense of completeness notion, the medical knowledge, the creation of categories linked to a normal pattern, the import of knowledge and the privatization of attention. The insistence we bringing these up issues, It is because we believe that is in the micro policy we can practice the daily revolutions, for purposes of crave more equitable relationships and committed to the complaint of stagnation.